Regionaldaten: Verknüpfungen ermöglichen - Thomas K. Bauer; Christina Gathmann; Ines Helm; Christian Raffer; Sebastian Siegloch; Sandra Schaffner; Andreas Lichter (Wirtschaftsdienst, 2023)
– Regional disparities are pronounced and persistent. Regional data of high quality are needed to improve the understanding of the origins and consequences of regional disparities and the effectiveness of regional policies through empirical analysis. Against the background of existing problems with regard to both the access to and the provision of high-quality regional data, this paper derives recommendations for action to improve the supply of regional data for the purpose of scientific analyses.
Keywords: R00; H00; C80; 330